نحو تخطيط ذكي الحكومة الذكية بديلاً عن الحكومة التقليدية - وليد صيداوي; حسان عيسى (Tishreen University, 2019)
The dependence on technology has increased significantly in various fields of life, leading to more complex cities in terms of structure and urban planning. This complexity presents in the need of Planning ,at various levels, to integrate its principles with the possibilities offered by the comprehensive database of existing structures in the city, whether infrastructure, social or economic structure. The research highlights the possibilities offered by the adoption of Smart Planning and the integration of modern technology in urban planning processes. It demonstrates the importance of the comprehensive database that monitors the current situation in different fields accurately and comprehensively, provides appropriate solutions to problems and offers flexible methods to adapt to changes in reality. The study examines one of the characteristics of Smart Planning, which is the smart government, explains its concept and methods of application, and shows the pros and cons that have emerged for this property and presents some examples of countries started with the adoption of smart government, and examines the possibility of implementation to develop our local reality. ازداد الاعتماد على التكنولوجيا في مختلف مجالات الحياة على نحو كبير، وأدّى ذلك إلى زيادة تعقيد المدن من حيث التركيب والتخطيط العمراني. تمثّل هذا التعقيد في حاجة التخطيط بمختلف مستوياته إلى دمج مبادئه مع الإمكانيات التي تقدمها قاعدة البيانات الشاملة للبنى الموجودة في المدينة، سواء البنية التحتية أو الاجتماعية أو الاقتصادية. يلقي البحث الضوء على الإمكانيات التي يقدّمها اعتماد التخطيط الذكي ودمج التكنولوجيا الحديثة بعمليات تخطيط المدن، ويوضح أهمية وجود قاعدة بيانات شاملة والتي تقوم برصد الواقع الراهن في مختلف المجالات بدقة وشمولية وتقدم الحلول المناسبة للمشكلات كما تقدم الأساليب المرنة للتوافق مع تغييرات الواقع. حيث يدرس البحث أحد خصائص التخطيط الذكي وهي الحكومة الذكية، ويوضّح مفهومها وأساليب تطبيقها، ويبين الإيجابيات والسلبيات التي ظهرت لتطبيق هذه الخاصة ويعرض بعض الأمثلة لدول بدأت باعتماد الحكومة الذكية، كما يدرس إمكانية تنفيذها لتطوير واقعنا المحلي.